Boost in Solid‐State Photon Upconversion Efficiency through Combined Approach of Melt‐Processing and Purification. Issue 6 (12th February 2022) - Raišys, Steponas; Juršėnas, Saulius; Kazlauskas, Karolis
Abstract : Realization of efficient photon upconversion (UC) mediated by triplet–triplet annihilation (TTA) in a solid state is a great challenge, even though order of magnitude higher efficiencies are routinely reported in a solution/liquid state. To address this issue in a typical emitter/sensitizer UC system, a combined approach is introduced based on 1) thorough emitter purification for reduced exciton quenching and 2) UC film fabrication via melt‐processing for attaining large emitter concentrations with suppressed aggregation. Emitter purification via vacuum sublimation is shown to reduce the number of both singlet and triplet quenchers as confirmed by fluorescence and UC quantum yield measurements along with the respective transient measurements performed on nanosecond and millisecond time domains. Application of this approach to the benchmark TTA‐UC system DPA/PtOEP is demonstrated to yield a record‐high UC efficiency (=8 ± 1%, out of maximum 50%) achieved at 40 wt% of DPA homogeneously dispersed in the PMMA host. Importantly, such high efficiency is accomplished in large‐area amorphous films, the most preferred for practical applications, and featuring low UC threshold (=5 mW cm −2 ) that is close to the solar irradiance. The presented approach describes the guidelines for boosting UC efficiency in the solid state, and generally, is applicable to any conventional TTA‐UC system. Abstract : Thorough emitter purification combined with the melt‐processing technique is a key for realization of highly efficient and fully solid large‐area amorphous photon upconverting (UC) films with the UC threshold close to solar irradiance.